Assessment of Haptoglobin 2-2 Genotype in Type 2 Diabetes and Cardiovascular Patients in North Indian Population: A Case-control Study - Puneet; Atul Kumar Upadhyay; Manpreet Kaur; Rattan Deep Singh (Journal of Clinical and Diagnostic Research, 2023)
Introduction: Haptoglobin (Hp), an acute phase protein, is a plasma inflammatory marker. It is important in both infectious and non infectious illnesses. When intravascular haemolysis occurs, the dead red blood cells are discharged into the circulation and link to Hp to form the haemoglobin (Hb)-haptoglobin (Hb-Hp) complex that is recognised by the macrophage scavenger receptor CD163. The Hp1 and Hp2 are its two alleles. The Hp2 is formed by a partial duplication of the Hp1 gene. The Hp1 has five exons, but Hp2 has seven exons owing to the duplication of Hp1 third and fourth exon. There are three genotypes of Hp: Hp1-1, Hp2-1, and Hp2-2. The encoded products of genotypes are attached to haemoglobin with varying degrees of affinity: Hp1-1 has the most affinity, Hp2-1 has medium affinity, and Hp2-2 has the lowest affinity. Hp allelic and genotypic variation differs amongst populations and different geographic regions of the world. Aim: To study the haptoglobin 2-2 genotype in type 2 diabetes and cardiovascular patients in north Indian population. Materials and Methods: It was a case-control study and a total of 200 participants were recruited randomly including 50 participants of type 2 Diabetes Mellitus (DM), 50 participants of Cardiovascular Disorders (CVD), 50 participants with Cardiovascular Disorders With type 2 Diabetes Mellitus (CVDWDM) and 50 normal healthy controls from Punjab Institute of Medical Sciences (PIMS) Hospital and clinics and Aashirwad laboratory of Jalandhar, Punjab, India in February 2021 to January 2022. Anthropometric variables were determined by using standard methods and biochemical parameters were measured by commercial available kits. Allele specific Polymerase Chain Reaction (PCR) or Amplification Refractory Mutation System (ARMS) PCR was used to detect Hp genotypes. Data were represented as mean±Standard Deviation and the statistical difference i.e. p<0.05 between all parameters was determined by using the Mann-Whitney U test. Results: Anthropometric parameters i.e. Body Mass Index (BMI) was found to be statistically significant in CVDWDM as compared to CVD, N and T2DM i.e. p=0.023, p=0.01 and p=0.014. Waist Circumference (WC) was found to be statistically significant in CVDWDM as compared to CVD, N and T2DM i.e. p=0.02, p=0.013 and p=0.012 and Hip Circumference (HC) was found to be statistically significant in CVDWDM as compared to CVD, N and T2DM i.e. p=0.02, p=0.017 and p=0.014. However, Apolipoprotein A1 mean value was found to be higher and statistically significant i.e. p=0.03 in Type 2 Diabetes Mellitus (T2DM) as compared to healthy participants. Triglycerides mean value was increased in T2DM as compared to CVD, CVD as compared to N and CVDWDM as compared to healthy controls (p-value=0.012,0.04,0.015, respectively). The findings had shown that a 349 bp band was detected in patients with T2DM, CVD and CVDWDM, implying that the Hp2-2 genotypes were observed but not in healthy controls. Conclusion: The study finds that people with DM, CVD, or CVDWDM all have a 349bp band. It means that the genotypes of the Hp2-2 allele were found in patients of diabetes, CVD and diabetics with CVD but not in the healthy individuals.